Africa-India Connections in Historical Perspectives. - Assié-Lumumba, N'Dri T. (African & Asian Studies, 2017)
It is a well-established historical fact that Africa and India have cultivated continuous connections for thousands of years. Exchanges of commodities produced on each side of the Indian Ocean in specific political, administrative, and geographic spaces have constituted the guiding thread of these relations. In the modern and contemporary periods, these relations have been shaped through European colonial establishments and their legacies in both sides. Past policies of forced migration and resettlement for economic exploitation of the British colonies in Africa, especially East and Southern Africa, became determinants of the Africa-India relations. The anti-colonial and decolonization struggles in Asia in general and specifically in India and Africa throughout the 20th century created opportunities for a new Africa-India cooperation. In these new relations, formal education, especially higher education, have been playing a prominent role. The thrust of this paper is to analyze the important role of higher education in a South-South cooperation framework between India and Africa as a continent or individual countries. The fluctuating or declining patterns of the number of African students pursuing their education in India in the past decade or so are analyzed.